Manner ethics addressed in existing accounting curriculum - Muhamad, Haslinah; Salleh, Arfah; Abu Kasim, Nor Aziah (Human Resource Management Academic Research Society, 2018)
This study was conducted to examine the manner in which ethics was addressed in the existing accounting curriculum, the content of syllabus by international business schools and instillation of ethics elements in the local universities’ vision and mission. Ethics syllabus of top 55 international business schools and 4 local universities web pages were reviewed. Summative content analysis was used to analyse the data. The results showed that not all universities involved in this study embedded ethics in their accounting curriculum as emphasised by IES 4, AACSB or MIA. In general, the content of current syllabi focuses on corporate governance. Issues regarding moral judgment, stewardship and accountability to shareholders are rarely discussed in ethics course as well as the element of human governance. This shows that the goal of ethics education is not on moral conversion, but on helping well-intentioned students to develop the skills necessary to identify and resolve their ethical dilemmas. Not all local public universities selected in this study encourage embedding ethics through their vision and mission. This is the sign that business schools do not show their commitment to centralise ethical responsibility at their corporate level.